Principal component analysis-based soil quality assessment of agronomic management practices in Marawi City, Philippines - ANALIZA C. OUANO; EDGEL O. ESCOMEN (Smujo International, 2026)
Abstract. Ouano AC, Escomen EO. 2026. Principal component analysis-based soil quality assessment of agronomic management practices in Marawi City, Philippines. Asian J Agric 10 (1): g100141. https://doi.org/10.13057/asianjagric/g100141. Soil Quality (SQ) is essential for agricultural sustainability and food security. This study evaluated 17 agricultural areas at the Mindanao State University Main Campus in Marawi City, Lanao del Sur, Philippines (MSU Main), using a Principal Component Analysis-based Soil Quality Index (PCA-SQI). Composite soil samples (0-20 cm depth) were analyzed for physical, chemical, and biological properties to identify associations with historical management practices. The PCA accounted for 78.00% of the cumulative variance. Ten indicators were retained from 17 measured parameters using PCA-based minimum data set selection criteria (silt, organic matter, pH, porosity, void ratio, volumetric moisture content, total nitrogen, clay, sand, and earthworm density) to formulate the SQI. Fifteen areas exhibited SQI values between 0.50 and 0.80 (medium suitability), while two severely degraded areas had indices of 0.4733 and 0.4932. Descriptive analysis revealed that areas subjected to continuous monocropping, conventional tillage, and exclusive synthetic fertilizer use were associated with lower SQI values, whereas sites employing integrated nutrient management and reduced tillage practices exhibited relatively higher soil functional capacity. Although statistical comparisons showed no significant differences across management categories (p>0.05), observable trends suggest that localized agronomic practices are descriptively associated with soil quality dynamics. Overall, the PCA-SQI framework provides a practical, site-specific diagnostic approach to evaluate soil functional status and highlights that integrating organic amendments and reducing tillage are vital for localized rehabilitation, though causal inferences remain limited by the observational study design.